Insight into Cross-Cultural Communication Barriers from the Perspective of Conversation Analysis - Sharipzianova, Faina (Division of Communication, University of Wisconsin-Stevens Point, 2020)
This research is designed with the intention of more deeply exploring the concept of cross-cultural communication barriers that have been recently looked upon mostly from the perspective of obvious larger cultural differences such as social norms defined by customs and traditions. A crucial facet of this study is drawing attention to the necessity of concretely defining the difference between the terms “language barriers” and “cross-cultural barriers” that are often, and arguably erroneously, used interchangeably, thus limiting their precision. Using linguistic and conversation analysis, this study looks at interactions between different groups of English speakers with varying cultural and linguistic backgrounds and observes the breakdowns in communication. The chosen approach of analyzing the intercultural interaction on the micro-level by spotting the sequential patterns and zooming in at the parts of the data where participants show signs of misunderstanding led to identifying three main ways in which cross-cultural barriers manifest themselves, namely the appearance of irrelevant turn, lack of recipient design, and unsuccessful collaborative completion.
Keywords: Conversation Analysis; Intercultural Communication; Communication Barriers; Language Barriers; Collaborative Completion; Recipient Design; Bilingual